(untitled) (Journal of Oriental Studies, 2019)
This work was supported by Japan Foundation Fellowship 2018 In this paper, an analysis of literature at the present stage on Korean issues in Japan is conducted. The author assumes consideration of the process of studying this issue in its development and change, in connection with the nature of the historical stage, the existence of a certain theory and methodology. The author believes that in connection with the changing historical conditions, as well as the opportunities and accessibility of primary sources, in the period after the 1990s, the focus remains on work related to the concept of “ethnic identity”, which became the focus of attention in the problems of Koreans in Japan. In addition, based on a qualitative review of the articles, the author believes that the question of the socioeconomic status of Koreans in Japan as a foreign citizen is gradually beginning to be investigated. The historical traumas of the Koreans as an “invisible minority” recede into the background, actualizing the modern process of naturalization and adaptation in Japanese society from the socioeconomic positions of the Korean community. Key words: Koreans in Japan, articles, analysis, identity, status.